Apex Magic Square Labeling for Complete Bipartite Graph and their application using Enigma - Madhu, C.S; Krishnappa, H.K; Sandeep, K.H; Dinesh, S (International Journal of Computer Sciences and Engineering, 2025)
Achieving better phases of security in transferring an image over LAN or internet and performance of enigma is depends on its efficiency based on time taken and the way it generates different graphs from a pixel. The most widely used algorithms are RSA, public key algorithm and other such algorithms does not provide full security to the cipher text, RSA is not going to assure the enigma while transforming the images. A better approach is to use Apex magic total Labeling (AMTL) of complete graph. It increases the efficiency by adding more extra security to the enigma systems. This method provides more security due to its difficulty in encryption in AMTL formation that cannot be easily found. This proposed research work provides an additional level of security to public key algorithms such as RSA, DH algorithm, etc. this approach is experimented in simulated systems like MATLAB.